PIGK defects induce apoptosis in Purkinje cells and acceleration of neuroectodermal differentiation - Siyi Chen; Jiali You; Xiaowei Zhou; Yan Li; Fang Liu; Yanling Teng; Hua Teng; Yunlong Li; Desheng Liang; Zhuo Li; Lingqian Wu (Cell Death and Disease)
Abstract Biallelic mutations in PIGK cause GPI biosynthesis defect 22 (GPIBD22), characterized with developmental delay, hypotonia, and cerebellar atrophy. The understanding of the underlying causes is limited due to the lack of suitable disease models. To address this gap, we generated a mouse model with PIGK deficits, specifically in Purkinje cells (Pcp2-cko) and an induced pluripotent stem cell (iPSC) model using the c.87dupT mutant (KI) found in GPIBD22 patients. Pcp2-cko mice demonstrated cerebellar atrophy, ataxia and progressive Purkinje cells loss which were accompanied by increased apoptosis and neuroinflammation. Similarly, KI iPSCs exhibited increased apoptosis and accelerated neural rosette formation, indicating that PIGK defects could impact early neural differentiation that confirmed by the RNA-Seq results of neural progenitor cells (NPCs). The increased apoptosis and accelerated NPC differentiation in KI iPSCs are associated with excessive unfolded protein response (UPR) pathway activation, and can be rescued by UPR pathway inhibitor. Our study reveals potential pathogenic mechanism of GPIBD22 and providing new insights into the therapeutic strategy for GPIBD.